The first successful bone marrow transplantation in Vietnam for a young Vietnamese boy with chronic granulomatous disease: a case report - Nguyen-Thanh, Binh; Nguyen-Ngoc-Quynh, Le; Dang-Thi, Ha; Le-Quynh, Chi; Nguyen-Thi-Van, Anh; Thuc-Thanh, Huyen; Dang-Anh, Duong; Lee, Pamela P.; Cao-Viet, Tung; Tran-Minh, Dien (Frontiers in Immunology, 2023)
Background: Chronic granulomatous disease (CGD) is an inborn error immunity disorder which results from defects in respiratory burst activity in phagocytes, leading to inability of killing of bacterial and fungal microorganisms. CGD patients usually had high incidence of morbidity such as infections, autoinflammatory disease and mortality. Allogeneic bone marrow transplantation is the only definitive cure for patients who suffer from CGD. Case presentation: We report the first transplant case of chronic granulomatous disease in Vietnam. A 25-month-old boy with X-linked CGD went through bone marrow transplantation from his 5-year-old, full-matched HLA carrier sibling after myeloablative conditioning regimen with busulfan 5.1 mg/kg/day for 4 days, fludarabin 30mg/m2/ day for 5 days and rATG (Grafalon- Fresenius) 10mg/kg/day for 4 days. Neutrophil engrafted on day 13 post transplant, donor chimerism was 100% on day 30 with the dihydrorhodamine- 1,2,3 flow cytometric assay test reached to 38% of normal 45 days post transplant. 5 months after transplant, patient was free of infection with stable DHR- assay at 37% and donor chimerism remained 100%. No sign of a graft- versus- host disease had been observed post transplant. Conclusion: We suggest that bone marrow transplantation is a safe and effectual cure for CGD patients, especially for patients with HLA-identical siblings.